Iron Deficiency Anemia in Pregnancy. (November 2015) - Di Renzo, Gian Carlo; Spano, Filippo; Giardina, Irene; Brillo, Eleonora; Clerici, Graziano; Roura, Luis Cabero
Anemia is the most frequent derailment of physiology in the world throughout the life of a woman. It is a serious condition in countries that are industrialized and in countries with poor resources. The main purpose of this manuscript is to give the right concern of anemia in pregnancy. The most common causes of anemia are poor nutrition, iron deficiencies, micronutrients deficiencies including folic acid, vitamin A and vitamin B12, diseases like malaria, hookworm infestation and schistosomiasis, HIV infection and genetically inherited hemoglobinopathies such as thalassemia. Depending on the severity and duration of anemia and the stage of gestation, there could be different adverse effects including low birth weight and preterm delivery. Treatment of mild anemia prevents more severe forms of anemia, strictly associated with increased risk of fetal–maternal mortality and morbidity.